A Critical Analysis of Corporate Governance: The Case of BlackRock - Czyżewski, Marcin (Krytyczna analiza ładu korporacyjnego na podstawie firmy BlackRock, 2024)
The aim of the article is to examine how BlackRock complies with corporate governance standards and whether it promotes them appropriately towards the companies in which it invests. To accomplish this, a critical review of the literature was employed, and later, qualitative research with documentation analysis in the form of articles available online, databases and reports was used. This article will focus on the history of the company, their “Aladdin” investment program, and many controversies that have arisen over the years, such as: investing in companies with a high ESG score and related inaccuracies; investments in businesses that produce huge amounts of pollution; companies from China that are blacklisted by the US as violating human rights; BlackRock’s role in the housing crisis; and connections with companies responsible for Amazon deforestation. This analysis will show us how BlackRock operates and its negative impact on the environment.
Czyżewski, M. (2024). A Critical Analysis of Corporate Governance: The Case of BlackRock. W J. Radomska & A. Witek-Crabb (Red.), New Trends in Business Management (s. 77–90). https://doi.org/10.15611/2024.30.7.06
Keywords: corporate governance; BlackRock; ESG; climate; Amazon deforestation; ład korporacyjny; klimat; wycinka lasów Amazonii